Stable expression of the cardiac sodium-calcium exchanger in CHO cells - Pijuan,V.; Zhuang,Y.; Smith,L.; Kroupis, C.; Condrescu,M.; Aceto,J.F.; Reeves,J.P.; Smith,J.B. (Am.J.Physiol, 1993)
A line of Chinese hamster ovary (CHO) cells called CK1.4 was produced by transfection with the gene for the bovine cardiac Na(+)-Ca2+ exchanger. CK1.4 cells stably expressed substantial exchange activity and exchanger protein as shown by immunoprecipitation. Exchange activity was quantified as 45Ca2+ influx that depended on both increasing intracellular Na+ and lowering the concentration of external Na+. Replacing external Na+ with K+ slightly increased 45Ca2+ uptake by CK1.4 cells with basal Na+ and greatly increased 45Ca2+ uptake by Na(+)-loaded cells. Neither exchange activity nor exchanger protein was detected in the nontransfected parental line. By contrast to CK1.4 cells, replacing external Na+ with K+ decreased 45Ca2+ uptake in the nontransfected cells whether or not they were Na+ loaded. Changes in cytosolic free Ca2+ determined with fura-2 were consistent with the 45Ca2+ uptake data. Analysis of poly(A)(+)-RNA by Northern blot confirmed that CK1.4 cells, but not the parental line, expressed the exchanger. Expression of the exchanger was also observed in aortic myocytes and a renal epithelial cell line (LLC-MK2) but not in other lines of renal epithelial cells (MDCK, LLC-PK1) or human dermal fibroblasts. The cardiac exchanger produced substantial 45Ca2+ efflux from CK1.4 cells in response to hormone-evoked release of stored Ca2+. CK1.4 cells are an attractive model for studies of the regulation of the cardiac exchanger because they stably express sufficient exchanger for biochemical and immunological analysis
Keywords: analysis; Animals; Aorta; Biological Transport,Active; calcium; Calcium Radioisotopes; Carrier Proteins; Cattle; Cho Cells; Cricetinae; Cytosol; genetics; Heart; Intracellular Fluid; isolation & purification; Kidney; Kinetics; metabolism; Methionine; Muscle,Smooth,Vascular; Ouabain; pharmacology; physiology; potassium; sodium; Sodium-Calcium Exchanger; Transfection